Resolution of fibromyalgia by controlling obstructive sleep apnea with a mandibular advancement device - Fernanda Vantine; Dominik Ettlin; Miguel Meira-e-Cruz (Sleep Science, 2021)
Fibromyalgia (FM) is a chronic, often disabling disorder characterized by multisite pain along with sleep problems and fatigue. Pain and sleep exhibit a reciprocal relationship. When FM and obstructive sleep apnea/hypopnea (OSA) co-exist, treatment options include continuous positive airway pressure or mandibular advancement device. We present a patient experiencing fibromyalgia and OSA whose symptoms vanished wearing a Mandibular Advancement Device (MAD) during sleep. To our knowledge, this is the first documented case of FM symptom resolution by MAD treatment.